Analysis of ESG Implementation at PT Wijaya Karya Based on ASRRAT 2024 - Salsabilla, Aura Shavina Unnov; Bhayangkara, Ida Bagus Ketut (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
Environmental, Social, and Governance (ESG) practices are increasingly important in supporting corporate sustainability, especially in infrastructure companies. This research aims to examine how PT Wijaya Karya (Persero) Tbk integrates ESG principles in its business operations. The research was conducted with a qualitative case study approach based on the company’s 2023 sustainability report which was analyzed using content analyzed using content analysis techniques. The results show that the implementation of ESG at WIKA reflects the company’s commitment to environmental protection, social responsibility, and good governance. This commitment is evidenced through the achievement of the Gold rating in ASRRAT 2024. The conclusion of this study is that the systematic implementation of ESG can improve corporate accountability and long-term stakeholder trust